1998
DOI: 10.1165/ajrcmb.19.6.3118
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Apoptosis during the Development and Resolution of Oleic Acid-Induced Acute Lung Injury in the Rat

Abstract: The oleic acid (OA) model of acute lung injury in rats is characterized by a massive and rapid influx of polymorphonuclear neutrophils (PMN) within 1 h, with a peak inflammatory response at 4 h and resolution by 72 h. We hypothesized that PMN apoptosis is involved in the resolution of OA-induced acute lung injury. To test this hypothesis, healthy adult Fischer 344 rats were given 30 microl OA in 0.1% bovine serum albumin (BSA) intravenously; controls were given BSA alone and killed at 1, 4, 24, and 72 h after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0
4

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(68 citation statements)
references
References 35 publications
3
60
0
4
Order By: Relevance
“…The serum collectin, MBL, did not significantly enhance phagocytosis. Because PMN apoptosis and subsequent phagocytosis by AMs are necessary for inflammation to be resolved (25)(26)(27), our data suggest that the pulmonary collectins may protect pulmonary tissue by facilitating the resolution of inflammation.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The serum collectin, MBL, did not significantly enhance phagocytosis. Because PMN apoptosis and subsequent phagocytosis by AMs are necessary for inflammation to be resolved (25)(26)(27), our data suggest that the pulmonary collectins may protect pulmonary tissue by facilitating the resolution of inflammation.…”
Section: Discussionmentioning
confidence: 83%
“…Several in vivo models of pulmonary injury demonstrate the importance of AM phagocytosis of apoptotic PMNs in the resolution of inflammation (25,26), and it has been suggested that chronic pulmonary inflammation may be a result of inefficient clearance of apoptotic PMNs (27). We hypothesize that when PMNs undergo apoptosis, the changes that occur at the PMN plasma membrane allow SP-A and SP-D to recognize them as nonself.…”
mentioning
confidence: 88%
“…The findings in the GTO-treated group are similar to those induced in OAinduced acute respiratory distress syndrome. 41,42 GTO treated rats also had renal failure evidenced by elevated serum blood urea nitrogen and TUNEL ĂŸ cells in the kidney tubules at the time of necropsy ( Figure 6B). Findings of drop out necrosis in these tubules supported progression to acute tubular necrosis.…”
Section: Intraductal Oaee Results In Lesser Systemic Injury Than Triomentioning
confidence: 98%
“…In animal models, induction of neutrophil apoptosis ameliorates ALI, 72 and the onset of neutrophil apoptosis coincides with the resolution phase of lung injury. 73 …”
Section: Epithelial Injurymentioning
confidence: 99%